Concept Lattice Theory in Data Mining and its Applications - MUSUMBU, KANINDA; SUNGU, Pascal; WANDJI, Nathalie (IJRDO -Journal of Computer Science Engineering, 2019)
Concept lattice has been proven to be a very eective tool and architecture for data mining in general. It is widely used for data analysis and knowledge discovery and various concept lattice based approaches are used depending on the type of data. This paper aims at presenting one application of the lattice theory : the text mining. In this approach, we applied the notion of lattice theory by using one of its components mostly used in data mining, the formal concept analysis which has a powerful method, the association rule extraction which helps to nd in a database patterns which appear frequently together.